Pemanfaatan Teknologi Dalam Pembelajaran Bilangan Dengan Pendekatan PMRI Pada Siswa Kelas Rendah Sekolah Dasar - If Only Dia Panjaitan; Nur Aini Putri; Zetra Hainul Putra (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
Mathematics is a subject that is always encountered from the lowest level of education to tertiary institutions, especially elementary schools to train logical, analytical, systematic and critical thinking. The learning process of mathematics, especially in the lower classes, is still in the concrete operational period and real situations. Therefore we need the right method to solve the problem of children who are lazy to learn because the methods used in learning mathematics still use books so that children are bored and prefer to play. The implementation of the description above is poured into technology in the form of an Android-based application as a medium for learning mathematics for children wherever and whenever, with a display of concrete and interesting images with music in the application. So that children are not easily bored with learning and easier to understand in learning mathematics, especially for low-grade classes with the guidance of parents at home. The purpose of this study to see the effectiveness of technology in learning mathematics. The research method is a qualitative method using interviews and observation on five students in junior class. The results of this study are students enjoy the learning process and understand in learning mathematics by using an android-based application rather than studying at school.